Gender Equality in Iranian History - Nasrin Rahimieh (International Institute of Islamic Thought, 2007)
This ambitious undertaking, comprising 6 chapters, 16 tables, 4 appendixes, and a glossary, is the culmination of a doctoral program at McGill University’s Institute of Islamic Studies. A specialist in Islam, world religions, and gender studies, Minoo Derayeh is now an assistant professor at York University in Toronto. Gender Equality in Iranian History seeks to uncover the social, political, and economic status of women across the vast expanse of Iranian history. In her “Foreword,” Ratna Gosh (McGill University) applauds the author’s contribution for showing that the “concept of Islamic feminism is founded on the idea of complementary rather than equal rights” and, equally importantly, for laying bare “the root of cultural patriarchy” (p. ii). The very idea of complementarity, as the book’s chapters reveal, has not always been unproblematically present in Iran’s encounter with Islam ...